The role of the addition of ovarian suppression to tamoxifen in young women with hormone-sensitive breast cancer who remain premenopausal or regain menstruation after chemotherapy (ASTRRA): study protocol for a randomized controlled trial and progress. Issue 1 (December 2016) - Kim, Hyun-Ah; Ahn, Sei; Nam, Seok; Park, Seho; Ro, Jungsil; Im, Seock-Ah; Jung, Yong; Yoon, Jung; Hur, Min; Choi, Yoon; Lee, Soo-Jung; Jeong, Joon; et al.
Abstract Background Ovarian function suppression (OFS) has been shown to be effective as adjuvant endocrine therapy in premenopausal women with hormone receptor-positive breast cancer. However, it is currently unclear if addition of OFS to standard tamoxifen therapy after completion of adjuvant chemotherapy results in a survival benefit. In 2008, the Korean Breast Cancer Society Study Group initiated the ASTRRA randomized phase III trial to evaluate the efficacy of OFS in addition to standard tamoxifen treatment in hormone receptor-positive breast cancer patients who remain or regain premenopausal status after chemotherapy. Methods Premenopausal women with estrogen receptor-positive breast cancer treated with definitive surgery were enrolled after completion of neoadjuvant or adjuvant chemotherapy. Ovarian function was assessed at the time of enrollment and every 6 months for 2 years by follicular-stimulating hormone levels and bleeding history. If ovarian function was confirmed as premenopausal status, the patient was randomized to receive 2 years of goserelin plus 5 years of tamoxifen treatment or 5 years of tamoxifen alone. The primary end point will be the comparison of the 5-year disease-free survival rates between the OFS and tamoxifen alone groups. Patient recruitment was finished on March 2014 with the inclusion of a total of 1483 patients. The interim analysis will be performed at the time of the observation of the 187th event. Discussion This study will provide evidence of the benefit of OFS plus tamoxifen compared with tamoxifen only in premenopausal patients with estrogen receptor-positive breast cancer treated with chemotherapy. Trial registration ClinicalTrials.gov IdentifierNCT00912548 . Registered May 31 2009. Korean Breast Cancer Society Study Group RegisterKBCSG005 . Registered October 26 2009.